2022
DOI: 10.1016/j.sciaf.2021.e01089
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing compliance with public health directives and support for government's actions against COVID-19: A Nigerian case study

Abstract: Because COVID-19 is a novel viral pandemic, there is a dearth of research in the body of evidence that explore factors that can influence compliance with public health recommendations and Nigerian government's actions to prevent the spread of COVID-19. Hence, this study's aim is to address this gap to help inform policymakers and the actions of public health leaders in Nigeria. The study included a sample of 336 adult Nigerians who responded to an online Qualtrics survey. Descriptive and linear regression anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 40 publications
0
9
0
1
Order By: Relevance
“…In addition, Mansoor (2021) implied that the government developing policies and solutions is essential to the public’s reactions to the pandemic. This leads to the public’s trust in the government being essential for this scenario [ 79 ]. The government maintains track of civilians’ thoughts, feelings, suffering, and dealing with the circumstance and how they perceive danger, emotions, and behavior in relation to the COVID-19 epidemic that is currently in effect.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Mansoor (2021) implied that the government developing policies and solutions is essential to the public’s reactions to the pandemic. This leads to the public’s trust in the government being essential for this scenario [ 79 ]. The government maintains track of civilians’ thoughts, feelings, suffering, and dealing with the circumstance and how they perceive danger, emotions, and behavior in relation to the COVID-19 epidemic that is currently in effect.…”
Section: Discussionmentioning
confidence: 99%
“…Strategies that highlight personal responsibility for health, and empower the public to take specific actions, have also demonstrated increased public response [ 20 , 21 ]. Interestingly, Wise et al highlighted risk perception as a predictor of protective health behaviours, as did a Nigerian study into compliance to COVID-19 public health directives [ 22 , 23 ]. The Warning Signs Campaign was produced by a credible medical association (The National Heart Foundation) and certainly provided specific instructions on how to respond to the outlined symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Two other studies that focused on evaluating the knowledge, intervention strategies and health practices among different segments of the Nigerian population revealed that the participants displayed a fair knowledge base and are poised to comply with the control measures and health practices, if available (Ejeh, Saidu, Owoicho, Maurice, Jauro et al, 2020;Doherty, Odeyemi, Adeola, Amolegbe & Ajagbe, 2020;Iloanusi, Iloanusi, Ajayi & Essien, 2021). A recent study also assessed citizens' reaction and compliance to COVID-19 directives Nigerian government revealed an association between stigmatization, COVID-19 threats, authority's capability and compliance (Nwakasi, Esiaka, Uchendu & Bosun-Arije, 2022). The closest to this study evaluated participants' risk perception as a critical factor in ensuring suitable preventive measures (Udomah, Ashaolu, Olomofe, Dada, Soyemi et al, 2021).…”
Section: Discussion Of Findingsmentioning
confidence: 99%